Erythrocyte Senescence in a Model of Rat Displaying Hutchinson-Gilford Progeria Syndrome - Manoj Kumar Chaudhary; Syed Ibrahim Rizvi (Analytical Cellular Pathology)
Background. Increased oxidative stress is a major cause of aging and age-related diseases. Erythrocytes serve as good model for aging studies. Dihydrotachysterol is known to induce premature aging feature in rats mimicking Hutchinson-Gilford progeria syndrome. Aim. In the present study, attempts have been made to explore the differential response of young and senescent erythrocytes separated by density gradient centrifugation from accelerated senescence model of rats mimicking Hutchinson-Gilford progeria syndrome and naturally aged rats. Methods. The erythrocytes of naturally aged and progeroid rats were separated into distinct, young and old cells on the basis of their differential densities. The parameters of oxidative stress and membrane transport systems were studied. Discussion and Conclusion. Our study provides evidence that organismal aging negatively affects oxidative stress markers and membrane transport systems in both young and old erythrocytes. This study further substantiates that the changes in progeria model of rats resemble natural aging in terms of erythrocyte senescence.